2020
DOI: 10.1101/2020.01.07.897389
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Information theory tests critical predictions of plant defense theory for specialized metabolism

Abstract: 1Different plant defense theories have provided important theoretical guidance in 2 explaining patterns in plant specialized metabolism, but their critical predictions remain to be 3 tested. Here, we systematically explored the metabolomes of Nicotiana attenuata, from single 4 plants to populations, as well as of closely-related species, using unbiased MS/MS analyses and 5 processed the abundances of compound-spectrum-based MS features within an information 6 theory framework to test critical predictions of Op… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 72 publications
2
12
1
Order By: Relevance
“…It was identified that, while JA is the central signal shaping the amplitude of convergent metabolic responses to both herbivories, ET fine-tunes the specificity of this metabolic response according to the herbivore diet breadth. The latter study, as in the present one, detected that phenolamides are the foliar metabolites whose production is most tightly dependent on the fine-tuning signaling function of ET (Li et al 2020). This convergence further reinforces a role of ET in mitigating the production of these metabolites according to insect herbivory type and echoes ecological implications suggested for the well-known function of ET in antagonizing the JA-dependent accumulation of nicotine when tobacco plants are attacked by nicotine-tolerant M. sexta larvae.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…It was identified that, while JA is the central signal shaping the amplitude of convergent metabolic responses to both herbivories, ET fine-tunes the specificity of this metabolic response according to the herbivore diet breadth. The latter study, as in the present one, detected that phenolamides are the foliar metabolites whose production is most tightly dependent on the fine-tuning signaling function of ET (Li et al 2020). This convergence further reinforces a role of ET in mitigating the production of these metabolites according to insect herbivory type and echoes ecological implications suggested for the well-known function of ET in antagonizing the JA-dependent accumulation of nicotine when tobacco plants are attacked by nicotine-tolerant M. sexta larvae.…”
Section: Discussionsupporting
confidence: 78%
“…In a recent large-scale metabolomics study, the degree of plasticity and diversity of the specialized metabolic profile of different Nicotiana species was investigated in response to herbivory by a "specialist" (M. sexta) and a "generalist" (Spodoptera littoralis, the cotton leaf worm) chewing insects (Li et al 2020). It was identified that, while JA is the central signal shaping the amplitude of convergent metabolic responses to both herbivories, ET fine-tunes the specificity of this metabolic response according to the herbivore diet breadth.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This transcriptional regulation usually depends on the transcription and translation of TFs [ 16 ], although other factors such as chromatin-remodeling could also be involved [ 17 ]. The transcriptional changes in, for example, metabolism-associated genes finally result in an altered metabolic profile of the attacked plant [ 16 , 18 ].…”
Section: Introductionmentioning
confidence: 99%